Aortic valve replacement vs. balloon-expandable and self-expandable transcatheter implantation: A network meta-analysis. (15th August 2021) - D'Ascenzo, Fabrizio; Bruno, Francesco; Baldetti, Luca; De Filippo, Ovidio; Marengo, Giorgio; Breviario, Susanna; Melillo, Francesco; Thyregod, Hans Gustav Hørsted; Thiele, Holger; Sondergaard, Lars; Popma, Jeffrey J.; Kodali, Susheel; et al.
Abstract: Introduction: Recently, observational data have raised concerns about safety of selfexpandable (SE) compared to balloon-expandable (BE) valves in TAVI, although potentially limited by patient selection bias. Methods. All Randomized Controlled Trials (RCTs) comparing BE vs. SE TAVI or/and vs. aortic valve replacement (AVR) were included and compared through Network Meta Analysis (NMA). All-cause and cardiovascular (CV) mortality were the primary endpoints, stroke, rates of permanent pacemaker implantation (PPI), moderate/severe paravalvular leak (PVL) and reintervention were the secondary endpoints. Results We obtained data from 11 RCTs, encompassing 9752 patients. After one and two years, no significant differences for allcause and CV mortality were observed. Compared to surgical bioprostheses, both BE and SE TAVI reduced the risk of acute kidney injury (OR 0.42; CI 95% 0.30–0.60 and OR 0.44; CI 95% 0.32–0.60), new-onset atrial fibrillation (OR 0.24; CI 95% 0.14–0.42 and OR 0.21; CI 95% 0.13–0.34) and major bleedings (OR 0.32; CI 95% 0.16–0.65 and OR 0.47; CI 95% 0.25–0.89). The BE prostheses reduced the risk of moderate/severe PVL at 30-day (OR 0.31; CI 95% 0.17–0.55) and of PPI both at 30-day (OR 0.51; CI 95% 0.33–0.79) and 1 year (OR 0.40; CI 95% 0.30–0.55) as compared to SE TAVI. Conclusions A TAVI strategy, independently from BE or SE prostheses, offers a midterm survival comparable to AVR. The BE prostheses are associated with a reduction of PPI and PVL compared to SE prostheses without any differences in all-cause and CV mortality during two years of follow up. PROSPERO ID CRD42020182407. Highlights: Observational data have raised concerns about safety of self-expandable (SE) compared to balloon-expandable (BE) valves. TAVI is confirmed to be a safe treatment strategy in all patients regardless of risk profile with severe aortic stenosis. SE prostheses are associated with higher pacemaker implantation and paravalvular leak compared to BE prostheses.